The Effect of Combination of Endorphin Massage and Murottal Therapy on Reduction of Menstrual Pain in Adolescent Girls at Al Azhaar Islamic High School Tulungagung - Niken Dwi Lusiani; Indah Maya Stasia (PT. Griya Eka Sejahtera, 2022)
Background: Menstrual pain can be reduced by pharmacological and non-pharmacological measures. Non-pharmacological treatments to reduce menstrual pain include endorphin massage and murottal therapy. This study aimed to determine the effect of endorphin massage and murottal therapy on reducing menstrual pain in adolescent girls at Al Azhaar Islamic High School Tulungagung.Methods: This study uses an observational analytical research design with an experimental approach. With purposive sampling technique, 18 respondents obtained a sample, the independent variable is endorphin massage and murottal therapy and the dependent variable is menstrual pain in adolescent girls before and after being given a combination of endorphin massage and murottal therapy. The Wilcoxon test statistic was used to determine the effect of the two variables.Results: Analysis using the Wilcoxon statistical test showed that p = 0.000 <0.05, then H0 was rejected and H1 was accepted, which means that there is an effect of a combination of endorphin massage and murottal therapy on reducing menstrual pain in adolescent girls at Al Azhaar High School Tulungagung.Conclusion: Endorphin massage technique combined with murottal therapy can stimulate the body to release and increase the production of endorphins and enkephalins which function to reduce menstrual pain, improve the mental system to reduce violent behavior showing body chemistry